The Roles of Asystasia gangetica (L.) T. Anderson and Ridge Terrace in Reducing Soil Erosion and Nutrient Losses in Oil Palm Plantation in South Lampung, Indonesia - Asbur, Yenni; Yahya, Sudirman; Murtilaksono, Kukuh; Sudradjat, Sudradjat; Sutarta, Edy Sigit Sutarta Sigit (Journal of Tropical Crop Science, 2016)
Asystasia gangetica (L.) T. Anderson is a weed commonly found on oil palm plantations and can be used as cover crop for mature oil palm plantations due to its tolerance to shading. The use of cover crop is  a soil conservation technique to support sustainable availability of soil nutrients by reducing erosion and nutrients loss, particularly during the rainy seasons. This research aims to determine the roles of A. gangetica as cover crop for measures against erosion and nutrients loss in mature oil palm plantation. This research was conducted in oil palm plantation, Unit Rejosari, PT Perkebunan Nusantara (PTPN) VII, District of Natar, South Lampung Regency from August 2014 to April 2015. The research used split block design in randomized complete block design with two factors and six replications. The main plots were ridge terrace, namely with and without ridge terrace. The sub plots were cover crops, namely with and without cover crops A. gangetica. The results show that using A. gangetica as cover crops in mature oil palm plantations effectively minimized erosion and loss of organic C, N, P, and K by 95.7%, 93.4%, 96.0%, and 90.0 %, respectively. The use of cover crop became more effective when combined with ridge terrace and reduced erosion by 94.1% and loss of organic C, N, P and K by 99.1%, 99.2%, 90.0% and 98.5%, respectively.